2007
DOI: 10.1007/s11257-007-9042-9
|View full text |Cite
|
Sign up to set email alerts
|

Mediation of user models for enhanced personalization in recommender systems

Abstract: Abstract. Provision of personalized recommendations to users requires accurate modeling of their interests and needs. This paper proposes a general framework and specific methodologies for enhancing the accuracy of user modeling in recommender systems by importing and integrating data collected by other recommender systems. Such a process is defined as user models mediation. The paper discusses the details of such a generic user modeling mediation framework. It provides a generic user modeling data representat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
124
0
3

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 173 publications
(136 citation statements)
references
References 55 publications
1
124
0
3
Order By: Relevance
“…Research on generic user modeling services [17], mediating user models [18], identifying users across system boundaries [19] and cross-system user modeling and personalization [20,21] further supports the re-use of user profiles in different application contexts. In this paper, we introduce a service that generates user profiles by exploiting Twitter and allows for applying these profiles in other applications.…”
Section: Related Workmentioning
confidence: 99%
“…Research on generic user modeling services [17], mediating user models [18], identifying users across system boundaries [19] and cross-system user modeling and personalization [20,21] further supports the re-use of user profiles in different application contexts. In this paper, we introduce a service that generates user profiles by exploiting Twitter and allows for applying these profiles in other applications.…”
Section: Related Workmentioning
confidence: 99%
“…On Facebook, users can explicitly declare their interests through profile features, association with groups and fan pages or through status line updates. Such attributes once extracted can be mediated [16] to ratings on items, for example: a user linking her profile to "Levis" fan page is essentially rating the brand and its products as favorable. The same process can be used for tweets (the name for a Twitter post), however methods such as sentiment analysis [17] are required in order to resolve the precise rating, since an open text sentence regarding "Levis" for example, can be a statement of endorsement or of hate.…”
Section: Mapping Social Web Services Contribution To Classical Recommmentioning
confidence: 99%
“…Some evaluations had shown that in certain conditions, user modeling data mediation improved the quality of recommendations, especially in the cold start of a recommender system [10].…”
Section: Related Workmentioning
confidence: 99%